Effects of nitric oxide on apoptosis and voltage‐gated calcium channels in human cardiac myofibroblasts. (10th October 2019) - Bae, Hyemi; Kim, Taeho; Lim, Inja
Summary: We characterised the voltage‐gated Ca 2+ channels (VGCCs) in human cardiac fibroblasts (HCFs) and myofibroblasts (HCMFs) and investigated the effects of nitric oxide (NO) on apoptosis and on these channels. Western blotting and immunofluorescence analyses show that α‐smooth muscle actin (a myofibroblast marker) was markedly expressed in passage (P) 12‐15 but not in P4 HCF cells, whereas calponin (a fibroblast marker) was expressed only in P4 cells. CaV 1.2 (L‐type) and CaV 3.3 (T‐type) of VGCCs were highly expressed in P12‐15 cells, but only weak CaV 2.3 (R‐type) expression was identified in P4 cells using reverse transcription‐polymerase chain reaction analysis. S‐Nitroso‐N‐acetylpenicillamine (SNAP, an NO donor) decreased cell viability of HCMFs in a dose‐dependent manner and induced apoptotic changes, and nifedipine (an L‐type Ca 2+ channel blocker) prevented apoptosis as shown with immunofluorescence staining and flow cytometry. Whole‐cell mode patch‐clamp recordings demonstrate the presence of L‐type Ca 2+ ( I C a, L ) and T‐type Ca 2+ ( I C a, T ) currents in HCMFs. SNAP inhibited I C a, L of HCMFs, but pre‐treatment with ODQ (a guanylate cyclase inhibitor) or KT5823 (a PKG inhibitor) prevented it. Pre‐treating cells with KT5720 (a PKA inhibitor) or SQ22536 (an adenylate cyclase inhibitor) blocked SNAP‐induced inhibition of I C a, L . 8‐Bromo‐cyclic GMP or 8‐bromo‐cyclic AMP also inhibited I C a, L . However, pre‐treatment with N‐ethylmaleimide (a thiol‐alkylating reagent) did not block the SNAP effect, nor did DL‐dithiothreitol (a reducing agent) reverse it. These data suggest that high concentrations of NO injure HCMFs and inhibit I C a, L through the PKG and PKA signalling pathways but not through the S ‐nitrosylation pathway.